The lost carnival : a Dick Grayson graphic novel - Moreci, Michael (DC Comics, 2020)
"Before Batman trained him to be Robin, Dick Grayson was star of his family of trapeze artists, but when an enchanting new attraction opens nearby and threatens to lure away their remaining customers, Dick is among those drawn to its magical glow and may be too mesmerized to recognize the dangers ahead."--Provided by publisher.